Soil heterogeneity in agricultural and natural ecosystems: relationships between anaerobic activity, organic matter, nutrients, and greenhouse gases - Brewer, Paul E., author; von Fischer, Joseph, advisor; Calderón, Francisco, committee member; Conant, Richard, committee member; Cotrufo, M. Francesca, committee member; Wallenstein, Matthew, committee member (Colorado State University. Libraries, 2017)
Many soil biogeochemical processes are difficult to predict, in part, due to the spatial heterogeneity of physical, chemical, and biological components of soil. Understanding how heterogeneity forms and affects biogeochemical processes is important because of the ultimate impacts on nutrient availability, carbon storage, and climate change. Oxygen and soil organic matter are two key components of soil microbial habitat, so I performed research to determine how the heterogeneity of each affect ecosystem functions. Oxygen can be absent in soil aggregates, litter patches, rhizospheres, and the guts of soil fauna, and when this occurs in unsaturated soils with oxic pore air these areas are referred to as anoxic microsites. The formation, persistence and impact of anoxic microsites are poorly characterized because these microsites are difficult to measure, especially across large areas that define ecosystem level processes. I studied what factors cause them to form and persist and how they affect C and N cycling and GHG fluxes. I performed focused, mechanistic laboratory studies of natural and agricultural soils, as well as field-scale studies of anoxic microsite effects in agricultural systems. In multiple studies, I circumvented the limitations and problems related to measuring soil oxygen or reduction-oxidation (redox) potentials at sub-millimeter scales instead by using gross CH4 production as an indicator of anoxic microsite presence and activity. I used two relatively recent methodological approaches to make gross CH4 measurements, CH4 stable isotope pool dilution for laboratory measurements and a CH4 process and transport model for field studies. I found that methanogenesis correlated with respiration, soil moisture, plant presence, and agricultural practice both in laboratory and field studies, indicating that the distribution of anoxic microsites is altered by climatic and land use factors in ways that are similar to the large-scale anoxic zones of wetlands. Methanogenesis was associated with elevated NH4+ concentrations and N2O flux, but lower NO3- concentrations. These relationships are consistent with slower nitrification and greater denitrification, so measurements of methanogenesis may be a useful proxy for other anaerobic processes. I also found evidence that consistent upland methanogenesis may stimulate methanotrophy (i.e., gross CH4 consumption) over the course of years, counterintuitively leading to an increase in net CH4 uptake. Finally, redox potential was not as strong an indicator of methanogenesis as expected, so I join others in concluding that redox potential may not be a desirable method for quantifying anoxic microsites. I also studied the effects of the spatial distribution of soil organic matter in the form of litter patches in soil. In a laboratory incubation, I manipulated the size and number of litter patches and soil moisture in a uniform mineral soil matrix. I found that dry soils with litter that was aggregated into larger patches exhibited greater rates of decomposition and nutrient availability, but that in wetter soils there were few effects of litter distribution. This complements my studies of anoxic microsites by showing that not only the presence of soil microsites, but variation in their size and distribution can also alter soil processes. In summary, my dissertation research concentrated on the causes and biogeochemical consequences of anoxic microsites and heterogeneity of organic matter in agricultural and natural ecosystems. My findings have increased our understanding of soil heterogeneity and the potential for it to cause significant changes in nutrient availability, decomposition, and greenhouse gas fluxes.
Keywords: decomposition; isotope pool dilution; tillage; greenhouse gases; anoxic microsites; methane